Subtitling for Social and Language Minorities: Subtitling of Oral Errors and Dialectal Features in the Case of Minoritised Languages - Martínez-Lorenzo, Mercedes (Journal of Audiovisual Translation, 2020)
Speakers of any (minoritised or majority) language sometimes make language mistakes. Bilingual speakers may use a hybrid language, mixing languages within a sentence or even within a word, especially when they are formally similar, as Spanish and Galician are. For minoritised languages, language errors may contribute to a negative perception towards the minoritised language. The Galician public broadcaster Televisión de Galicia (TVG) has received criticism for not being a high-quality language model, permitting the intrusion of language mistakes in its content. From an exclusively linguistic viewpoint, these errors should be corrected in subtitling. Conversely, subtitling guides and target users favour a verbatim rendition of the audio, in which oral language mistakes should not be corrected. Dialectal features, even if they are not considered errors, are non-standard language. This paper aims at answering the question of “to correct or not to correct” oral errors and dialectal features in the case of minoritised languages. It presents the most relevant data from a literature review, and an analysis of subtitling guidelines & standards and of current practices at TVG. These results have yielded an original protocol for the correction or reproduction of oral errors according to speech control, target audience and broadcast genre, the effect of a mistake, and the type of language error (vocabulary vs. grammar).